2017
DOI: 10.1542/peds.2016-1403
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioglioma Arising From Desmoplastic Medulloblastoma: A Case Report and Review of Literature

Abstract: We describe a case of medulloblastoma maturating into ganglioglioma during therapy. A 10-month-old boy was diagnosed with a desmoplastic medulloblastoma and was treated with gross total resection followed by induction chemotherapy. A recurrence in the tumor bed during therapy was managed with focal radiation therapy and consolidation chemotherapy. After further progression, the recurrent tumor was resected completely. The histopathology revealed a benign ganglioglioma with no residual medulloblastoma. This cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…We identified five publications that reported six cases of histologically confirmed MB with post-treatment maturation (4 boys, 2 girls) (Tables 1 and 2). [4][5][6][7][8] The patients' mean age was 7.8 years (range, 3 months to 11 years). The MB subtypes were DMB (n¼2), MBEN (n¼1), CMB (n¼1), and unclassified (n¼2).…”
Section: Literature Searchmentioning
confidence: 99%
“…We identified five publications that reported six cases of histologically confirmed MB with post-treatment maturation (4 boys, 2 girls) (Tables 1 and 2). [4][5][6][7][8] The patients' mean age was 7.8 years (range, 3 months to 11 years). The MB subtypes were DMB (n¼2), MBEN (n¼1), CMB (n¼1), and unclassified (n¼2).…”
Section: Literature Searchmentioning
confidence: 99%
“…Disease dissemination is an early event in MB, with up to ∼40% of patients showing metastases at diagnosis, with poor survival. Metastatic disease and tumor recurrence are responsible for the low survival rates, and those who survive frequently show treatment-related adverse effects (5,20,35,36,38,40,(50)(51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
“…The Neuropathological results for the 20 children in our study were desmoplastic medulloblastoma, some cases with poorly differentiated small cells with Homer-Wright Rosette and perivascular pseudo-Rosette showing lobular pattern with regions of dense intercellular reticulin and nodular reticulin-free zones, with moderate desmoplasia. Chelliah D et al and santosh Valvi et al found that desmoplastic medulloblastoma is common in paediatric age less than 3 years and has better prognosis (23,24), while Rubinstein LJ et al found that the desmoplastic type occur commonly in adult patients in the cerebellar hemispheres (40% laterally located) and that the classical type occurred in children and commonly is the midline (32).…”
Section: Discussionmentioning
confidence: 99%